Legal Protection of Pauman Land in Karangasem District - BUDIADNYANA, I Gusti Putu; SUWITRA, I Made; SUKANDIA, I Nyoman (Indonesia Strategic Sustainability, 2025)
This paper examines the legal status and registration of Pauman land in the Karangasem Regency of Bali. The concept of Pauman land is unique to this region and is considered a gift from the King of Karangasem. Recently, there have been disputes over the registration of Pauman land as individual plots through PTSL, leading to questions about its legal status and ownership. The study uses an empirical legal approach, including statute, historical, case, analytical, conceptual, and legal sociology approaches. The research highlights the gap between the predetermined norm and the implementation of Pauman land practices. Pauman cannot be considered a legal entity that can hold land rights under state law, but it can be recognized as a subject of the Temple according to the Decree of the Minister of Home Affairs. The paper recommends issuing a Certificate of Property Rights (SHM) in the name of the Temple to strengthen the position of Pauman land ownership without changing its communal and cultural heritage status. The use of the Temple's subject name is preferable to borrowing the name Klian for registering Pauman land as communal property. The study also predicts potential disputes due to re-recognition by the puri family, which needs to be anticipated by Pauman. Overall, this paper provides insights into the unique legal status and registration of Pauman land in the Karangasem Regency of Bali and offers recommendations to ensure the preservation of its communal and cultural heritage status.